The Impact of Flash Sales, Free Shipping, and Price Discounts on Impulse Buying Behavior among Gen Z Consumers - Mirelle Gavania Addiba; Muhammad Rizky Effendi; Rhesyakha Syadza Syach; Nindya Anindita Husnaa Tanaya Dahlan (Asosiasi Ahli Administrasi Indonesia, 2026)
Generation Z customers in Bandung, Indonesia, are more likely to make impulsive purchases on the Shopee platform due to the quick growth of e-commerce and the growing use of marketing strategies like flash sales, free shipping, and price reductions. This study aims to examine how flash sales, free delivery, and price reductions affect Generation Z customers' impulsive purchasing habits. The quantitative survey approach was the research technique employed. Purposive sampling was used to choose 200 student replies as participants. To investigate the association between variables, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that, either partially or concurrently, flash sales, free delivery, and price reductions have a favorable and significant impact on impulsive purchasing behavior. Because of the urgency and FOMO (fear of missing out) that buyers felt, flash sales were the best predictor of these factors. Additionally, rather than viewing free delivery and price reductions as two distinct marketing strategies, Generation Z customers typically view them as one way to save money. These findings provide useful implications for e-commerce businesses in developing more successful promotional tactics and add to the empirical understanding of the influence of integrated promotional signals on impulsive purchase decisions in the setting of digital commerce.